1993
DOI: 10.1364/ao.32.005153
|View full text |Cite
|
Sign up to set email alerts
|

Six-stage digital free-space optical switching network using symmetric self-electro-optic-effect devices

Abstract: We describe the design and demonstration of an extended generalized shuffle interconnection network, centrally controlled by a personal computer. A banyan interconnection pattern is implemented by use of computer-generated Fourier holograms and custom metallization at each 32 × 32 switching node array. Each array of electrically controlled tristate symmetric self-electro-optic-effect devices has 10,240 optical pinouts and 32 electrical pinouts, and the six-stage system occupies a 9 in. × 12.5 in. (22.9 cm × 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…The emergence of electrically controlled optical modulators based on novel effects in quantum-well structures [36], including the family of devices known as self-electrooptic-effect devices (SEED's) [37], [38] and the development of vertical-cavity surface-emitting lasers (VCSEL's) (see, e.g., [39] and [40] for recent representative examples), were particularly important because they offered viable optoelectronic output devices for fabrication in large numbers in arrays. The optoelectronic device arrays and smart pixels stimulated significant work on array optical systems (see, e.g., [41]), leading to some large system demonstrations based on the SEED technology with, e.g., tens of thousands of light beams in a functioning digital system [42].…”
Section: A Historical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of electrically controlled optical modulators based on novel effects in quantum-well structures [36], including the family of devices known as self-electrooptic-effect devices (SEED's) [37], [38] and the development of vertical-cavity surface-emitting lasers (VCSEL's) (see, e.g., [39] and [40] for recent representative examples), were particularly important because they offered viable optoelectronic output devices for fabrication in large numbers in arrays. The optoelectronic device arrays and smart pixels stimulated significant work on array optical systems (see, e.g., [41]), leading to some large system demonstrations based on the SEED technology with, e.g., tens of thousands of light beams in a functioning digital system [42].…”
Section: A Historical Backgroundmentioning
confidence: 99%
“…Many of these techniques have been recently reviewed in [49]. References [28], [42], and [50]- [59] give examples of free-space systems investigated for optical interconnect applications. Waveguides on silicon chips have been investigated [60]- [62], though complete systems using these are not yet demonstrated.…”
Section: A Historical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a challenge, this is within the capabilities of current optomechanical technology. 23 A full diffractive-based analysis of the alignment tolerances of a clustered-window relay will be the subject of a later publication.…”
Section: Dt 1202mentioning
confidence: 99%
“…Moreover, several research groups are building system prototypes of such optoelectronic MINs 13 . For example, we have designed an optoelectronic perfect shuffle MIN and shown that this design outperforms both chip-level and multichip module (MCM) level be used).…”
Section: Introductionmentioning
confidence: 99%